Foundation design of embankments constructed on Connecticut Valley varved clays / by Charles C. Ladd. - Massachusetts. Department of Public Works.; United States. Federal Highway Administration.; Massachusetts Institute of Technology. Department of Civil Engineering. Constructed Facilities Division.; Ladd, Charles C. (Charles Cushing) (Tufts University. Tisch Library., 2019)
1 online resource (438 pages) : illustrations.; Prepared for Commonwealth of Massachusetts Department of Public Works in cooperation with U.S. Department of Transportation Federal Highway Administration.; This report is made available as part of the Dr. Charles C. Ladd Collection. For more information, contact Dr. Lewis Edgers (ledgers@tufts.edu) or Dr. Jack Germaine (john.germaine@tufts.edu) in the Tufts University Civil and Environmental Engineering department.